Descriptive and Prospective Analysis of Young Adult Alcohol Use and Romantic Relationships: Disentangling between- and within-Person Associations Using Monthly Assessments. (10th November 2018) - Fleming, Charles B.; Lee, Christine M.; Rhew, Isaac C.; Ramirez, Jason J.; Abdallah, Devon Alisa; Fairlie, Anne M.
ABSTRACT: Background : Prior research on romantic relationships and alcohol use among young adults has not distinguished between differences in patterns of relationship status over extended periods of time and within-person changes in status that only occur for some individuals. Objectives : This study captured between-person differences in relationship patterns, assessed associations between relationship patterns and alcohol use, and examined within-person associations between alcohol use and relationship status changes. In addition, age and sex differences in between- and within-person associations were tested. Methods : We used multilevel modeling of monthly data collected over one year on alcohol use and romantic relationship status from a Seattle area community sample of 620 young adults (ages 18–24). Results : Participants were coded into six relationship pattern groups: (1) single-not-dating (16%), (2) stable-in-a-relationship (30%), (3) single-dating (10%), (4) ended-a-relationship (14%), (5) started-a-relationship (13%), and (6) ended-and-started-a-relationship (18%). Single-not-dating and stable-in-a-relationship groups reported the least drinking across the entire year; the single-dating, ended-a-relationship, and ended-and-started-a-relationship groups reported higher levels of drinking. Examining within-person changes in groups 3–6 revealed increases in drinking associated with months of dating among the single-dating group, months postbreakup among the ended-a-relationship group, and months of breaking up and starting a new relationship among the ended-and-started-a-relationship group. Few differences by age or sex were found for between- or within-person associations. Conclusions : The findings point to heterogeneity in patterns of relationship status over time, differences in relationship patterns associated with variations in drinking, and particular time points of elevated risk for young adults who experience changes in status.